Histopathological pattern of gastric biopsies of Helicobacter pylori positive patients in Sardjito General Hospital, Yogyakarta - Putut Bayupurnama (The Indonesian Society for Digestive Endoscopy, 2000)
Objective: To determine the gastric histopathological types of H. pylori positive patients. Materials and Methods: Study design was prospective study. Consecutive patients who were suffering chronic dyspepsia underwent endoscopic examination between August 1998 and December 1999. The biopsy specimens were taken from the gastric antrum and corpus and sent to the pathologist for histopathological typing and H. pylori examinations. H. pylori were also confirmed with CLO and IgG- Helicobacter pylori test. Results: There were 92 patients (48 male (M) and 44 female (F)) who underwent endoscopical gastric biopsies between August 1998 and December 1999. Fifty six (60.87%) patients suffered from chronic superficial gastritis, 11 (11.96%) from chronic atropic gastritis, 2 (2.17%) from chronic gastritis with metaplasia, 3 (3.27) from gastric ulcer, and 2 (2.17%) from gastric signet-ring cell carcinoma. Twenty one (22.8%) patients was found to be H. pylori positive based on histopathologic examination with CLO and IgG-H. pylori tests. Those were 5 (8.90%) patients with chronic superficial gastritis, 7 (63.63%) chronic atrophic gastritis, 3 (100%) gastric ulcer, 2 (100%) chronic gastritis with metaplasia, 1 (50%) signet-ring carcinoma. The age range of the H. pylori positive patients were between 16 and 76 years old. Conclusion: There were twenty one (22.8%) H. pylori positive patients out of 92 endoscopied patients and a high percentage tendency of H. pylori positively in chronic atrophic gastritis, gastric ulcer, and chronic gastritis with metaplasia, although most of the patients had chronic superficial gastritis. Further study with larger sample is needed to get clearer picture of H. pylori distribution based on gastric histopathological types. Key words: histopathological type, gastric biopsy, H. pylori, gastritis